Entrepreneurship and entrepreneurial education in the context of postgraduate nursing - Fernanda Hannah da Silva Copelli; Alacoque Lorenzini Erdmann; José Luís Guedes dos Santos; Dirce Stein Backes; Jussara Gue Martini (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective To understand entrepreneurship and entrepreneurial education in the context of postgraduate nursing. Method Qualitative study based on Grounded Theory. The theoretical sample consisted of 15 master's and doctoral students and seven professors from a postgraduate nursing program at a university in southern Brazil. Individual interviews were conducted between August/2018 and February/2019 in a location defined by the participants, in general the University. The data were collected and analyzed simultaneously by initial and focused coding. Results Three categories and 11 subcategories emerged that, interrelated, represented the phenomenon "Glimpsing entrepreneurship and entrepreneurial education in postgraduate nursing". Conclusion Entrepreneurship and entrepreneurial education, in the context of postgraduate nursing, were understood as incipient and promising processes. In this sense, it is necessary to intensify studies to demonstrate the entrepreneurial possibilities of the area.